2022
DOI: 10.3389/fphys.2022.783251
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Benefits of Exercise in Patients With Multiple Sclerosis and COVID-19

Abstract: Multiple sclerosis (MS) is a demyelinating disease characterized by plaque formation and neuroinflammation. The plaques can present in various locations, causing a variety of clinical symptoms in patients with MS. Coronavirus disease-2019 (COVID-19) is also associated with systemic inflammation and a cytokine storm which can cause plaque formation in several areas of the brain. These concurring events could exacerbate the disease burden of MS. We review the neuro-invasive properties of SARS-CoV-2 and the possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 355 publications
0
4
0
Order By: Relevance
“…The positive effects of regular exercise on the brain were found to be related to restored neurotransmission and remyelination, to the refining of BBB-integrity, and to the improvement of the immune responses [ 5 , 195 ] as well as to mitigating effects on chronic inflammation and autoimmunity [ 196 , 197 ]. The improved BBB-permeability was reached through changes in proteins of the tight junctions, in the supporting activity of surrounding astrocytes, and in oxidative capacity of microglia, as well as by decreasing of inflammation [ 198 , 199 ].…”
Section: Search For Therapeutic Strategies: Modulatory Effect Of Bioa...mentioning
confidence: 99%
See 2 more Smart Citations
“…The positive effects of regular exercise on the brain were found to be related to restored neurotransmission and remyelination, to the refining of BBB-integrity, and to the improvement of the immune responses [ 5 , 195 ] as well as to mitigating effects on chronic inflammation and autoimmunity [ 196 , 197 ]. The improved BBB-permeability was reached through changes in proteins of the tight junctions, in the supporting activity of surrounding astrocytes, and in oxidative capacity of microglia, as well as by decreasing of inflammation [ 198 , 199 ].…”
Section: Search For Therapeutic Strategies: Modulatory Effect Of Bioa...mentioning
confidence: 99%
“…It has been demonstrated that physical activity may buffer the effects of psychosocial stress induced by COVID-19 and improve mental and physical health among the population [ 5 , 201 ]. Therefore, regular physical exercise may possibly mitigate mental and psychological impairments related to the long COVID syndrome by improving the neuroimmune homeostatic conditions, including balanced interactions between neuromodulatory cytokines and neurotransmitters, opioids, and neurotrophic and growth factors.…”
Section: Search For Therapeutic Strategies: Modulatory Effect Of Bioa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, regarding the expression of ACE2 on microvascular endothelial cells and vascular smooth muscles, SARS-CoV-2 disrupts the relationship between endothelium and smooth muscles which results in disordered vasodilation and vasoconstriction as well as disorders in gas exchange [ 73 ]. It has been documented that some central autoimmune diseases are susceptible to other diseases involving immune system [ 74 , 75 ]. MS is a chronic central disease characterized by inflammatory demyelination.…”
Section: Introductionmentioning
confidence: 99%